2013
DOI: 10.1017/dmp.2013.82
|View full text |Cite
|
Sign up to set email alerts
|

Response of General Practitioners to Infectious Disease Public Health Crises: An Integrative Systematic Review of the Literature

Abstract: GPs' response to public health crises in different countries presents potential for improving pandemic preparedness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 26 publications
(91 reference statements)
1
32
0
4
Order By: Relevance
“…Evaluation of healthcare system responses to earlier infectious pandemics shows various approaches and different levels of involvement of primary care in different countries, but generally a non-optimal preparedness. [6][7][8] Difficulties in supply and use of PPE, healthcare decisions such as prioritisation of high-risk patients, support from authorities, lack of knowledge and training and the emotional burden, are factors that compromise an effective response to a pandemic. In past years, various and divergent preparedness plans have been developed in different countries.…”
Section: Open Accessmentioning
confidence: 99%
“…Evaluation of healthcare system responses to earlier infectious pandemics shows various approaches and different levels of involvement of primary care in different countries, but generally a non-optimal preparedness. [6][7][8] Difficulties in supply and use of PPE, healthcare decisions such as prioritisation of high-risk patients, support from authorities, lack of knowledge and training and the emotional burden, are factors that compromise an effective response to a pandemic. In past years, various and divergent preparedness plans have been developed in different countries.…”
Section: Open Accessmentioning
confidence: 99%
“…It is important for health care systems to recognize the value of a strong coordinated response to this crisis from a primary health perspective, 2 with best practices that are transferable across nations. This is essential given that the early presentation of COVID-19 infection is nonspecific, with most patients presenting to primary health care clinics with mild upper respiratory tract symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that GPs' training skills can effectively increase the value of community health services. For example, it helps for more active participation in cancer screen, the management improvement of systemic diseases, and better solution to the epidemic public health crisis [2,3,4,5]. In China, because the reputation of community health care institutions nowadays is still far lower than the large general hospitals, the patient's trust in the level of community health service technology is relatively low, and the amount of medical visits is not high, which leads to the serious lack of willingness of GPs to invest in medical efforts [6].…”
Section: Introductionmentioning
confidence: 99%